Macrophyes pacoti n. sp. (Araneae: Anyphaenidae) from Brazilian Atlantic Forest, with notes on an araneopathogenic fungus - Brescovit, Antonio D.; Villanueva-Bonilla, German A.; Sobczak, Jullyana Cristina M. S. M.; de Sousa Nóbrega, Francisco A.; Oliveira, Luiz Fernando M.; Arruda, Italo Diego Paiva; Sobczak, Jober F. (Zootaxa, 2019)
The spider genus Macrophyes O. Pickard-Cambridge, 1893 includes five species from the Neotropical region (World Spider Catalog 2019). Two species were described from Central America, M. attenuata, the type species, by Pickard-Cambridge (1893), known until now only by the male, and M. elongata by Chickering (1937) know by both sexes. Three other species were described from South America, M. silvae Brescovit, 1992 and M. manati Brescovit, 1993 from Peru, and M. jundiai Brescovit, 1993 from Brazil (Brescovit 1992, 1993). Brescovit (1997) diagnosed this genus from other Anyphaeninae by the cylindrical abdomen, retrolateral margin of the chelicera with prominent distal tooth, close to the claw and by the tibia of the male palp almost twice longer than the cymbium. The females could be confused with Mesilla Simon by the long and cylindrical abdomen, but are distinguished by the epigynum with narrow, sinuous lateral borders and, internally, by the long copulatory ducts (see Brescovit, 1997: figs 146, 150−151).